A New and Accurate Map of the World, Comprehending all the New Discoveries, in Both Hemispheres, carefully brought down to the Present Time. - Baldwyn, George Augustus
This map shows the entire world in two round depictions of the Eastern and Western Hemispheres, respectively. Each of the major regions is outlined, shaded, and labeled. Major rivers and islands are marked. There are several small drawings around the outside of the map showing "Geographical Circles," the "Solar System," and the "Terrestrial Globe."